Modelling and simulation of Fe2O3/aluminum thermite combustion - Brito, Paulo (2010)
We present a one-dimensional model to simulate self-propagating high-temperature synthesis processes. The radial combustion of Fe2O3/Al thermite is used as case study. The model considers non-steady propagation with conductive/radiative heat transfer mechanisms and zero order kinetics. The thermophysical properties of the components depend on the temperature and composition of the mixture and appropriate mixing rules are used for each property. Fixing the thermophysical properties for the initial conditions, we conclude that increasing K leads to higher maximum temperatures and wave propagation velocities, always with complete conversion. The simulation results are in good agreement with the experimental observations. The activation of the thermophysical properties variation causes numerical difficulties which are being solved by further tuning of the parameters.